The Effect of Fraction Board Learning Media on Students' Learning Outcomes in Mathematics at SDN 08 Tiumang - Ratnawati; Dwi Novri Asmara; Delvi Suryanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research was motivated by the mathematics learning process that has not been optimal, as it has not yet utilized engaging learning media. As a result, students’ learning outcomes have been unsatisfactory. Therefore, this study aimed to apply fraction board learning media to help students achieve learning objectives more effectively. The purpose of this study is to determine the influence of fraction board learning media on students' learning outcomes in mathematics at SDN 08 Tiumang. This study employed a Pre-Experimental Design using the One Group Pretest–Posttest type. The design involved only one group, which was the experimental group from the third grade at SDN 08 Tiumang. The data collection technique used was testing. Furthermore, data analysis was conducted using SPSS 25, which involved two stages: a normality test and a hypothesis test. The results of the study indicate that the implementation of the fraction board learning media positively affected the mathematics learning outcomes of third-grade students at SDN 08 Tiumang. This is evidenced by the students' posttest scores. In the normality test, if the significance value is greater than 0.05, the data is normally distributed; if it is less than 0.05, the data is not normally distributed. The normality test results showed a pretest significance value of 0.889 > 0.05 and a posttest significance value of 0.966 > 0.05, indicating that the learning outcome data in the experimental class is normally distributed. Furthermore, the hypothesis test using the paired sample t-test at a 95% significance level (α = 0.05) showed that the p-value (sig. 2-tailed) was 0.000 < 0.05. According to the hypothesis testing criteria, this means that Ha is accepted and Ho is rejected.